PERCEPTIONS OF FISHERMEN'S COMMUNITY REGARDING RELIGIOUS EDUCATION IN NIBUNG HANGUS DISTRICT BATU BARA - Wawan Akbar; Ika Wardani (Journal of Educational Science Learning and Research, 2024)
In this study, the authors found information about the perception of the fishing community in the Nibung Hangus sub-district, Baru Bara district, that the fishing community in the village considered religious education very important, but their working time became an obstacle in providing religious education in their families. This study aims to: (1) find out how the perception of the fishing community in Nibung Hangus Subdistrict, Batu Bara Regency regarding religious education, (2) explain how religious education in the fishing community in Nibung Hangus Subdistrict, Batu Bara Regency, (3) explain what are the problems of education religion in the fishing community, Nibung Hangus District, Batu Bara Regency. This research belongs to the type of qualitative research, this qualitative research is descriptive by interpreting a phenomenon that occurs. The subjects in this study were parents who work as fishermen, children, religious leaders, community leaders, youth leaders and village heads. In the process of data collection, researchers used data collection methods, namely observation, interviews, and documentation. From the results of this study, it can be concluded that the perceptions of the fishing community in Ujung Kubu Village are: (1) The fishing community says that religious education is very important, (2) some fishing families apply religious education optimally as less than optimal, (3) some children carry out religious education. teachings from parents and teachers regarding religious education